A novel single-phase-to-earth fault location method for distribution network based on zero-sequence components distribution characteristics. (November 2018) - Rui, Liang; Nan, Peng; Zhi, Yang; Zare, Firuz
Highlights: Distribution features of zero-sequence components is used to locate faults. Simplified distibuted parameter model is adopted to reduce the computational burden. A fault factor considering voltage sag is defined to select the fault feeder. Simulation results confirmed the advantages of the method. Abstract: Based on distribution characteristics of the zero-sequence voltages and currents of the distributed lines, this paper proposes a novel single-phase-to-earth fault (SPTEF) location scheme for distribution network. Firstly, the distributed parameter model of distribution feeder lines is appropriately simplified according to Taylor series expansion of the hyperbolic functions in the model. The fault factor is constructed to select the faulted feeder. Then, the distribution features of the zero-sequence voltage (ZV) along the feeder line are analyzed. In each section of the faulted feeder, golden section search algorithm is adopted to distinguish the faulted section. Finally, based on the concept of maximum fault current, accurate fault location is realized by genetic algorithm (GA). A radial distribution network model containing different types of distribution lines is established in PSCAD/EMTDC. The calculation results of MATLAB prove the validity, reliability and accuracy of the proposed fault location scheme.